Optically stimulated Al2O3:C luminescence dosimeters for teletherapy: Hp(10) performance evaluation. (May 2018) - Hashim, S.; Musa, Y.; Ghoshal, S.K.; Ahmad, N.E.; Hashim, I.H.; Yusop, M.; Bradley, D.A.; Kadir, A.B.A.
Abstract: The performance of optically stimulated luminescence dosimeters (OSLDs, Al2 O3 :C) was evaluated in terms of the operational quantity of H P (10) in Co-60 external beam teletherapy unit. The reproducibility, signal depletion, and dose linearity of each dosimeter was investigated. For ten repeated readouts, each dosimeter exposed to 50 mSv was found to be reproducible below 1.9 ± 3% from the mean value, indicating good reader stability. Meanwhile, an average signal reduction of 0.5% per readout was found. The dose response revealed a good linearity within the dose range of 5–50 mSv having nearly perfect regression line with R 2 equals 0.9992. The accuracy of the measured doses were evaluated in terms of operational quantity H P (10), wherein the trumpet curve method was used respecting the 1990 International Commission on Radiological Protection (ICRP) standard. The accuracy of the overall measurements from all dosimeters was discerned to be within the trumpet curve and devoid of outlier. It is established that the achieved OSL Al2 O3 :C dosimeters are greatly reliable for equivalent dose assessment. Highlights: We evaluate the performance of Al2 O3 :C OSL dosimeters using Co-60 irradiations. The reproducibility (< 2%), 0.5% signal reduction and dose linearity up to 50 mSv were reported. We determine the H p (10) measurements accuracy (< 7%) using the trumpet curve analysis.